2020
DOI: 10.1038/s41598-020-74299-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genotypes of Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. in household, shelter, breeding, and pet market dogs in Guangzhou, southern China

Abstract: Cryptosporidium spp., Giardia duodenalis, and Blastocystis sp. are common intestinal protozoans that infect humans and animals worldwide. A survey that assessed the prevalence, molecular characteristics, and zoonotic potential of these pathogens was conducted on a variety of dogs in Guangzhou, southern China. A total of 651 canine stool samples from household (n = 199), shelter (n = 149), breeding (n = 237), and pet market dogs (n = 66) were collected from eight districts in Guangzhou. Cryptosporidium spp., Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…PERMANOVA was also applied to assess the similarities of microbial communities as a function of gender, age, and box in both distance matrices. None of these other variables were significantly associated with microbiota composition (gender: p = 0.4453; age: p = 0.2073; box: p = 0.0535), which is consistent with previous studies [ 13 , 20 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…PERMANOVA was also applied to assess the similarities of microbial communities as a function of gender, age, and box in both distance matrices. None of these other variables were significantly associated with microbiota composition (gender: p = 0.4453; age: p = 0.2073; box: p = 0.0535), which is consistent with previous studies [ 13 , 20 ].…”
Section: Resultssupporting
confidence: 91%
“…The prevalence is higher in young animals (between 9 and 14 weeks of age, 62.4%) compared to puppies between 5 and 8 weeks of age (30.4–32.6%) [ 10 , 11 , 12 ]. Animals living in communities, for example, in shelters or breeding kennels, are more frequently positive than privately owned pets, due to the high density of animals in these facilities [ 4 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study further shows that animals that were regurlarly treated for the helminth infestations were at low risk of acquiring the cryptosporidium infection. Our finding is in agreement with a study by (Liao et al, 2020) who indicated that deworming was a protective factor against cryptosporidiosis. This could be attributed to the fact that different antihelminth drugs that are often administered to the animals exerts a static (limiting growth) and/or cidal (killing) effects on the cryptosporidium pathogen.…”
Section: Discussionsupporting
confidence: 94%
“…Blastocystis was not detected in any canine or feline stool sample in our study. Similarly, Blastocystis infection has not been found in dogs in Spain [ 61 ], Greece [ 60 ], Japan [ 64 ], China [ 56 ], Australia [ 34 , 52 ], USA [ 69 ], or Brazil [ 54 , 71 ]. In a dozen or so other studies, Blastocystis in dogs was detected over a wide frequency range, from 1.3% to 70.8% ( Table 1 ), and sometimes up to 100% of dogs were infected; however, these were small groups of three to five animals (data not included in the table) [ 35 , 70 , 90 ].…”
Section: Resultsmentioning
confidence: 99%